2010
DOI: 10.1128/mcb.00165-10
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of the Mitochondrial Protein Voltage-Dependent Anion Channel Is Coupled to the Induction of Apoptosis

Abstract: Accumulating evidence implicates that the voltage-dependent anion channel (VDAC) functions in mitochondrion-mediated apoptosis and as a critical player in the release of apoptogenic proteins, such as cytochrome c, triggering caspase activation and apoptosis. The mechanisms regulating cytochrome c release and the molecular architecture of the cytochrome c-conducting channel remain unknown. Here the relationship between VDAC oligomerization and the induction of apoptosis was examined. We demonstrated that apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
252
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(260 citation statements)
references
References 65 publications
6
252
1
1
Order By: Relevance
“…VDAC1 Oligomeric State and Conformational Changes Realized upon Apoptosis Induction-Recently, using chemical cross-linking and BRET2, we demonstrated that the oligomeric assembly of VDAC1 in cultured cells is highly enhanced upon induction of apoptosis by various inducers, all of which act via mitochondria but through different mechanisms (28,29). These and other findings led us to propose that VDAC1 exists in a dynamic equilibrium between monomeric and oligomeric forms that shifts toward oligomerization upon apoptosis induction.…”
Section: ␤-Strands 8 and 16 Play Role In Structuring Vdac1mentioning
confidence: 88%
See 2 more Smart Citations
“…VDAC1 Oligomeric State and Conformational Changes Realized upon Apoptosis Induction-Recently, using chemical cross-linking and BRET2, we demonstrated that the oligomeric assembly of VDAC1 in cultured cells is highly enhanced upon induction of apoptosis by various inducers, all of which act via mitochondria but through different mechanisms (28,29). These and other findings led us to propose that VDAC1 exists in a dynamic equilibrium between monomeric and oligomeric forms that shifts toward oligomerization upon apoptosis induction.…”
Section: ␤-Strands 8 and 16 Play Role In Structuring Vdac1mentioning
confidence: 88%
“…Indeed, using chemical cross-linking, we demonstrated that the oligomeric assembly of VDAC1 in cultured cells is highly enhanced (up to 20-fold) upon induction of apoptosis by various agents (e.g. STS, curcumin, As 2 O 3 , etoposide, cisplatin, TNF-␣, H 2 O 2 , UV irradiation, or VDAC1 overexpression), all of which act via mitochondria but through different mechanisms (28,29). Moreover, when we employed bioluminescence resonance energy transfer (BRET2) to monitor VDAC1 oligomerization in living cells, we noted that incubation with apoptosis inducers enhanced the BRET2 signal, whereas exposure to apoptosis inhibitors prevented this enhancement (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Short hairpins (sh) targeting two nonoverlapping sequences within the coding region of human VDAC1 were designed based on previously published sequences (62,63). The shRNA was created using the following complementary sets of PAGE-purified oligonucleotides (Integrated DNA Technologies): VDAC1 sh1 forward (5′-TCACTAGGCACCGAGA-TTATTTCAAGAGAATAATCTCGGTGCCTAGTGTTTTTTC-3′), VDAC1 sh1 reverse (5′-TCGAGAAAAAACACTAGGCACCGAGATTATTCTCTTGAAATAATCTCGGTG-CCTAGTGA-3′); VDAC1 sh2 forward (5′-TGTGACGGGCAGTCTGGAATTTCAA-GAGAATTCCAGACTGCCCGTCACTTTTTTC-3′), VDAC1 sh2 reverse (5′-TCGA-GAAAAAAGTGACGGGCAGTCTGGAATTCTCTTGAAATTCCAGACTGCCCGTC-ACA-3′).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, VDAC1 was previously identified as a TG2 substrate in PMA-stimulated H9c2 cells [27]. It may be that TG2-mediated amine incorporation into HK1 and VDAC interferes with the ability of these proteins to interact with each other and modulate cardioprotection and/or cell survival [64]. It is also notable that ANP32A functions as an inhibitor of protein phosphatase 2A and thus may regulate ERK1/2 and PKC; therefore it is conceivable that its modification by TG2…”
Section: In Situ Modulation Of Tg2 Activity and Detection Of Tg2 Protmentioning
confidence: 99%